Relationship between Young Citizens Democracy Education and Good Governance - Fuad, Varidlo (International Journal of Educational Qualitative Quantitative Research, 2023)
The sustainability of a country depends on the quality of the next generation, which plays a vital role in various aspects of life, ranging from education, culture, economy, politics, and religion. Education can build a new generation of a nation towards a better direction. All nations worldwide are trying to prepare the next generation of good and smart citizens. Carrying the spirit of democracy, all nations worldwide emphasize organizing a good governance government and focusing on the involvement of its citizens. On this basis, it is important to know the involvement of young citizens in the implementation of good governance both at the local and national levels. This study aims to see the relationship between young citizens democracy education and the implementation of good governance. This research is quantitative research through a correlational analysis method. The sample in this study was 119 respondents from student university at Indonesia.  The results showed that there was a positive and significant relationship between between young citizens democracy education and the implementation of good governance. This research contributes to proving that the democratic education of young citizens has a vital role in shaping the next generation of good and smart citizens.